Pengaruh Konsentrasi Asap Cair Bambu Tabah (Gigantochloa nigrociliata Buse-Kurz) dan Lama Perendaman Terhadap Kesegaran Pisang Cavendish (Musa Acuminata) - K. Justikha Natalia Praja; Pande Ketut Diah Kencana; I Gusti Ketut Arya Arthawan (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2021)
Cavendish banana one of the horticultural products that are prone to physiological setbacks and very vulnerable to physical damages after harvest. Various concentrations of tabah bamboo liquid smoke with different soaking times can use as natural preservatives. The bananas used in this study were Cavendish bananas from Buleleng, every bunch consists of at least ten banana with a length of 18.59 cm and a weight of 125 ± 5 g. This study aims to find the best treatment combination of the treatmentoof liquid smoke concentration and soaking time to maintain freshness and shelf life of Cavendish bananas during storage. The experimental design used in this study was a Completely Randomized Design (CRD) with two factors, the first factor was the concentration of tabah bamboo liquid smoke, and the second factor was the soaking time. The first factor consists of four levels of concentration namely 1%, 3%, 5%, and 7%. The second factor consists of three levels of soaking time, namely 10 minutes, 20 minutes and 30 minutes with storage temperature using room temperature (28 ± 2oC). The parameters observed in this study are: repiration rate, weight loss, hardness, level of damages, TPT and organoleptics. The best interaction results are shown in the treatment of 7% concentration of tabah bamboo liquid smoke with 10 minutes of soaking with an average value of respiration rate parameters of 51.18 ml CO2 / kg.hour, an average value of weight loss with a value of 17.61%, an average value of hardness of 3.82 kg, the average value of TPT was 15.65% Brix, the value of the level of damage was 2.40, the average organoleptic value of taste was 4.67, aroma was 4.54 and color was 3.87. The conclus of this study indicates that the combination of A4B1 (7% tabah bamboo liquid smoke concentration with soaking for 10 minutes) is the best combination to keep freshness and the quality of green bananas until the storage period of the 15th day.